PENERAPAN MEDIA GACHA BERBASIS GAME BASED LEARNING UNTUK MENINGKATKAN KEBUGARAN JASMANI SISWA KELAS VIII SMP DALAM PEMBELAJARAN PJOK - Angelia Damayanti, Dita; Ekawati, Ratna; Wahyudi, Soni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research investigates the effectiveness of the Game Based Learning (GBL) strategy supported by gacha media in enhancing the physical fitness of eighth-grade students at a state junior high school in Malang, within the context of Physical Education, Sport, and Health (PJOK) instruction. The study adopted a Classroom Action Research (CAR) framework grounded in the Kemmis and McTaggart cyclical model, structured into two cycles each comprising two learning sessions. Research participants consisted of 32 female students from class 8G during the 2025/2026 academic year. Physical fitness assessment utilized the Indonesian Physical Fitness Test (TKJI) designated for the 13–15 age bracket, complemented by structured observation instruments, photographic documentation, and field notes. Data analysis combined quantitative calculations—including component mean scores, class total scores, and inter-cycle mastery percentages—with qualitative descriptive interpretation. Findings revealed a steady and notable upward trend in students' physical fitness throughout the intervention. The aggregate class score progressed from 451 (56.38%) in the baseline measurement to 499 (62.38%) in Cycle I, ultimately reaching 602 (75.25%) in Cycle II, thereby surpassing the established Minimum Mastery Criterion (KKM) of 75%. The distribution of TKJI performance categories also shifted considerably: in Cycle II, 81.25% of participants achieved the "Good" classification and 6.25% reached "Very Good," a marked contrast to the pre-cycle condition in which 43.75% of students fell within the "Poor" category. These outcomes indicate that the Game Based Learning strategy with gacha media constitutes an effective instructional approach for raising student engagement levels and advancing physical fitness outcomes within PJOK learning environments.